Study of the practice of mental physical activity on psychosocial factors in health education applicants - Puertas-Molero, Pilar; Ubago-Jiménez, José Luis; Zurita-Ortega, Ana; Melguizo-Ibáñez, Eduardo (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
The practice of physical activity has been shown to have numerous physical and mental health benefits. This study aimed to investigate the relationship between the practice of mental physical activities and levels of stress, burnout syndrome, and emotional intelligence among competitive examiners in education. An ex post facto comparative study was carried out on a sample of 4117 health education examiners. The instruments used were the Perceived Stress Scale, the Maslach Burnout Inventory and the Trait Meta-Mood Scale. The data reveal that the practice of mental physical activity helps to reduce the levels of burnout and stress in the opposition population. In conclusion, it is affirmed that mental physical activity is a sporting practice that helps to reduce negative mental states.